1998
DOI: 10.1021/la970669s
|View full text |Cite
|
Sign up to set email alerts
|

Human Growth Hormone Adsorption Kinetics and Conformation on Self-Assembled Monolayers

Abstract: The adsorption process of the recombinant human growth hormone on organic films, created by self-assembly of octadecyltrichlorosilane, arachidic acid, and dipalmitoylphosphatidylcholine, is investigated and compared to adsorption on silica and methylated silica substrates. Information on the adsorption process of human growth hormone (hGH) is obtained by using total internal reflection fluorescence (TIRF). The intensity, spectra, and quenching of the intrinsic fluorescence emitted by the growth hormone's singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 26 publications
3
31
0
Order By: Relevance
“…The contact angles of the OTS and EDA surfaces are in good agreement with literature values [14,16]. The contact angles attained for the phospholipid headgroups, however, are rather high, a possible result from monolayer rearrangement in the presence of the captive air bubble [13]. The higher contact angle for cationic Et-DPPC monolayers versus the DPPS and DPPC monolayers is attributed to a less dense packing due to steric hindrance and charge repulsion.…”
Section: Fluorescence and Scanning Force Microscopy (Sfm)supporting
confidence: 88%
See 2 more Smart Citations
“…The contact angles of the OTS and EDA surfaces are in good agreement with literature values [14,16]. The contact angles attained for the phospholipid headgroups, however, are rather high, a possible result from monolayer rearrangement in the presence of the captive air bubble [13]. The higher contact angle for cationic Et-DPPC monolayers versus the DPPS and DPPC monolayers is attributed to a less dense packing due to steric hindrance and charge repulsion.…”
Section: Fluorescence and Scanning Force Microscopy (Sfm)supporting
confidence: 88%
“…In a recent study we demonstrated that LB films with greater mobility adsorbed less human growth hormone than surfaces of similar chemistry but decreased mobility [13]. We attributed this effect to an unfavorable loss of surface conformational entropy upon protein adsorption.…”
Section: Sfm Imaging Of Adsorbed Tmvmentioning
confidence: 79%
See 1 more Smart Citation
“…Nanostructures of thiol molecules serve as templates for attaching proteins. Selectivity of protein adsorption can be achieved by using the variation in protein affinity toward different SAMs (52)(53)(54)(55)(56)(57)(58).…”
Section: High-resolution Imaging and Fabricationmentioning
confidence: 99%
“…Since each of the two fluorescence contributions to the total fluorescence intensity can be separately determined in experiments and the concentration of the af488-HSA solution, c Sol , is known, the surface concentration of surface bound af488-HSA, Γ HSA , can, in principle, be calculated by finding the optical relationship between the two fluorescence components, I Ads and I Sol . The conversion from I Ads and I Sol to Γ HSA used in this study paralleled the quantification of protein adsorbed amount in total internal fluorescence microscopy [30,31] and will not be described in detail here (data not shown). The error in the measurement of the adsorbed HSA surface density was up to ±3.5% (estimated from the standard deviations of protein fluorescence intensity measured within OTS bands).…”
Section: Fluorescence Image Processing and Analysismentioning
confidence: 99%